Smart Home Resilien Berbasis Edge Computing untuk Sistem IoT Arus Lemah Menggunakan Protokol MQTT (IJM: Journal of Multidisiplinary, 2025)
Conventional smart home systems are highly dependent on internet connectivity, which often leads to functional failures when network disruptions occur. This study develops a resilient smart home system based on edge computing using the MQTT protocol and low-power IoT devices (ESP32). Data processing is performed locally at the edge node, allowing the system to continue operating even during complete internet outages. The research method employed is experimental testing under three network conditions: stable internet, unstable network, and total internet disconnection. The evaluated parameters include system resilience, communication latency, functional reliability, and power consumption. The experimental results demonstrate that the edge-based system maintains 92–100% operational functionality during internet outages, achieves low latency of 20–40 ms, and consumes a maximum power of only 0.17 W. These findings confirm that the integration of edge computing and MQTT is an effective approach for improving reliability, energy efficiency, and operational stability in low-power smart home systems.